'Radicalisation: the journey of a concept', revisited. (April 2018) - Silva, Derek M. D.
Over the past decade, radicalisation has emerged as perhaps the most pervasive framework for understanding micro-level transitions towards violence. However, the concept has not only become a dominant policing framework, but also an overarching governmental strategy encompassing surveillance, security, risk and community engagement. The emergence of this strategy has been accompanied by a whole host of analysts, advisers and scholars, who claim to possess 'expert' knowledge of individual transitions towards political violence. Revisiting 'Radicalisation: the journey of a concept', Arun Kundnani's 2012 typology of such 'expertise' ( Race & Class, doi 10.1177/0306396812454984), the author comparatively examines scholarly developments in relation to 'radicalisation' and juxtaposes new knowledge claims with official government counter-radicalisation strategies and funding programmes in the UK, US and Canada to highlight how some of the most problematic knowledge claims continue to influence social policy as we move forward in the global 'war on terror'.